The impact of customs and traditions on joint diseases Research in medical anthropology (Journal of the College of Basic Education, 2022)
Our research is labeled "the impact of customs and traditions on joint diseases". Which falls within the topics of medical sociology is only an attempt by which we hope to view and analyze the causal relationship between customs and traditions and arthritic diseases, so this research came to highlight these diseases after the increase in the incidence of it to the fold of what it was in the past, And the social and cultural factors that were behind the injury and as a result the impact of this serious disease on the individual and society as a whole, especially after we knew the nature of this disease and what it may leave to the injuries of young age groups and the average age and productive production, construction and giving to his family, Which it offers to the community and the nation in general